Foreign Currency Loans and Systemic Risk in Europe - Pinar Yesin (Swiss National Bank, Study Center Gerzensee, 2013)
Foreign currency loans to the unhedged non-banking sector are remarkably prevalent in Europe and create a significant exchange-rate-induced credit risk to European banking sectors. In particular, Swiss franc (CHF)-denominated loans, popular in Eastern European countries, could trigger simultaneous bank failures if depreciation of the domestic currencies prevents borrowers from servicing the loans. Foreign currency loans thus pose a systemic risk from a "common market shock" perspective. The author uses a novel dataset of foreign-currency loans from 17 countries for 2007-11 (collected by the Swiss National Bank) and builds on the method suggested by Ranciere, Tornell, and Vamvakidis (2010) to quantify this systemic risk. The author finds that systemic risk is substantial in the non-euro area, while it is relatively low in the euro area. However, CHF-denominated loans are not the underlying source of the high systemic risk: Loans denominated in other foreign currencies (probably to a large extent in euros) contribute significantly more to the systemic risk in the non-euro area than CHF-denominated loans. Furthermore, systemic risk shows high persistence and low volatility during the sample period. The author also finds that banks in Europe have continuously held more foreign-currency-denominated assets than liabilities, indicating their awareness of the exchange-rate-induced credit risk they face.
Keywords: F3; G2; 330; Unhedged bank loans; Exchange rate induced credit risk